O jogo das alíquotas de pis/cofins e o preço do combustível: análise da (in) constitucionalidade do decreto 9.101/2017 - Ponte, Andrine de Araújo (Universidade Federal Rural do Semi-Árido, 2018)
The objective of this study is the legal analysis of the changes in the rates of PIS- PASEP and COFINS contributions promoted by various decrees since the enactment of Laws 10,865 of 2004 and 11,727 of 2008, in respect of petroleum products and ethanol respectively ; focusing on the last Decree issued by President Michel Temer on the subject, 9,101 of July 20, 2017, which restored the value of the rates on fuels derived from petroleum to the levels established by the Law. It was also sought to establish, a parallel between the changes introduced by the Decree and their compatibility with the tax principles of strict legality in tax matters and of nonagesimal anteriority. Given this scenario, the paper aims to discuss the practices of the Executive Branch in the area of taxation, seeking to bring to light what it bases, verifying that there is consistency with the constitutional text or if the legal system was used only as a tool for the consolidation of the political agenda / government economy.
Artigo Acadêmico
Keywords: Alíquotas de PIS e COFINS sobre combustíveis; Constitucionalidade do decreto 9.101; Princípio da anterioridade nonagesimal; Princípio da legalidade tributária; Rates of PIS and COFINS on fuels; Constitutionality of decree 9.101; Principle of nonagesimal anteriority; Principle of tax legality; CIENCIAS SOCIAIS APLICADAS::DIREITO